History and happiness on Notes from underground and Civilization and Its Discontents - Maciel, Marta Maria Aragão; Calou, Ângela (Sofia, 2026)
This paper aims to present, in general terms, the relationship between the notions of history and happiness in the works Notes from Underground (1864) and Civilization and Its Discontents (1929), in order to signal the confluence of perspectives between the images of the Russian writer Fyodor Dostoyevsky (1821-1881) and the conceptual framework of the Austrian thinker Sigmund Freud (1856-1939). To this end, the monologue of the character "the underground man" is addressed, exposing the critique of the idealistic optimism of his historical time embodied in the figure of the radical theorist Nikolai Chernyshevsky (1828-1889). Then, the Freudian vision of the relationship between the individual and society is thematized, given under the sign of a fundamental and, therefore, insurmountable tension between instinctive freedom and the demands of maintaining social experience. From this, the elective affinity between the images of one and the concepts of the other is concluded, signaled in the refusal of the idea of progress as the evident destiny of reason, which delegitimizes the affirmation of a necessary link between history and happiness.
Keywords: history; happiness; progress; Dostoievsky; Freud; raison